Proceedings of the 27th ACM SIGKDD Conference on Knowledge Discovery &Amp; Data Mining 2021
DOI: 10.1145/3447548.3467150
|View full text |Cite
|
Sign up to set email alerts
|

Would Your Tweet Invoke Hate on the Fly? Forecasting Hate Intensity of Reply Threads on Twitter

Abstract: Curbing hate speech is undoubtedly a major challenge for online microblogging platforms like Twitter. While there have been studies around hate speech detection, it is not clear how hate speech finds its way into an online discussion. It is important for a content moderator to not only identify which tweet is hateful, but also to predict which tweet will be responsible for accumulating hate speech. This would help in prioritizing tweets that need constant monitoring. Our analysis reveals that for hate speech t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(26 reference statements)
1
12
0
1
Order By: Relevance
“…A few research looked into how hate speech spreads through social media. In a recent discussion, Dahiya et al [12] discussed the necessity of anticipating the hatred intensity of tweets. Lin et al [38] classified the tweets into different levels of hatred and suggested the HEAR model track posts that are likely to cause hate speech.…”
Section: Hate Speech Detection In Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…A few research looked into how hate speech spreads through social media. In a recent discussion, Dahiya et al [12] discussed the necessity of anticipating the hatred intensity of tweets. Lin et al [38] classified the tweets into different levels of hatred and suggested the HEAR model track posts that are likely to cause hate speech.…”
Section: Hate Speech Detection In Social Mediamentioning
confidence: 99%
“…where 𝑐 𝜑 𝑖 refers to the 𝑖 𝑡ℎ reply. As the replies in the original dataset have no ground-truth hate intensity, we quantify the hate intensity of each reply using a weighted sum of two measures as suggested in [12]:…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the conversational design of social media wherein users can reply to a given comment (either support, refute or irrelevant to the original message), the build-up of threads in response to a hateful message can also intensify hate even if the reply is not hateful on its own. The evolution of such hate intensity has shown diverse patterns and no direct correlation to the parent tweet which makes the task of hate speech detection more difficult [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to lack of resources for Marathi we catalogue 9 a list of profane words in Marathi and use this to find the fraction of profane words in a tweet. For Hindi, we curate a list of profane words by collating and appending to existing lists 10 , and use this to score each tweet. As for the sentiment of the tweet, we incorporated off-theshelf HuggingFace models to obtain the positive, negative and neutral scores for a tweet 11 12 .…”
Section: Hindi and Marathi Classifiermentioning
confidence: 99%